Which of the following is an equation with one constant, two coefficients, and three terms? 3x - 4y = 5x; 3x - y = 5y; 3x - 4y = 5y; 3x - 4 = 5y

1 answer

To identify the equation that has one constant, two coefficients, and three terms, let's analyze each option:

  1. 3x - 4y = 5x

    • This can be rearranged to: \(3x - 5x - 4y = 0\) → \(-2x - 4y = 0\), which means it has two coefficients (for \(x\) and \(y\)), and a total of three terms (the terms being \(-2x\), \(-4y\), and \(0\)). But there's no constant on the left side of the equation.
  2. 3x - y = 5y

    • Rearranging gives us: \(3x - 6y = 0\), which involves two coefficients (for \(x\) and \(y\)) and three terms (the terms are \(3x\), \(-6y\), and \(0\)). No constant present.
  3. 3x - 4y = 5y

    • Rearranging results in: \(3x - 4y - 5y = 0\) → \(3x - 9y = 0\). This also has two coefficients (for \(x\) and \(y\)) and three terms (\(3x\), \(-9y\), and \(0\)). No constant present.
  4. 3x - 4 = 5y

    • Rearranging gives us: \(3x - 5y - 4 = 0\). Here, there are two coefficients (for \(x\) and \(y\)), one constant term (-4), and three terms (\(3x\), \(-5y\), and \(-4\)).

From the analysis above, the equation 3x - 4 = 5y fits the requirements perfectly as it has one constant (-4), two coefficients (3 and -5), and three terms (\(3x\), \(-5y\), and \(-4\)).

Therefore, the answer is 3x - 4 = 5y.